MENGKAJI PENERAPAN SANKSI PIDANA DALAM PENCEGAHAN PENYEBARAN COVID-19 DI INDONESIA - Prakarsa, Aliyth; Herli, Dadang; Yulia, Rena (UI Scholars Hub, 2021)
The police in handling policies that are applied in an emergency period use criminal sanctions, meanwhile, the police also need to provide education and legal protection for the community when there are repressive efforts from the police in enforcing government policies through the Chief of Polices Declaration. The specific target to be achieved is to examine the application of the Chief of Polices Declaration in the application of the contents of the edict that contains criminal sanctions and examine its effectiveness in its application. The method used in this study is a normative and empirical legal research method. Normative research is carried out by reviewing library data which is secondary data, in the form of government policies in handling the Corona Virus Disease (Covid-19) Public Health Emergency which is then related to the application of the Decree of the Chief of the Police of the Republic of Indonesia Number: Mak/2/III/2020 concerning Compliance with Government Policy in Handling the Spread of the Corona Virus (Covid-19) in an effort to enforce it through legal channels by means of criminal sanctions.